Teaching critical thinking to Chinese students in English as a foreign language writing class: A review - Xiaomeng Zeng; Latha Ravindran; Mansour Amini (International Journal of Evaluation and Research in Education (IJERE), 2023)
Critical thinking (CT) is important for English as a foreign language (EFL) writing. However, the EFL writings of Chinese students are usually negatively commented on in terms of CT in writing. The study reviewed relevant studies on how CT in writing was taught to Chinese EFL learners at the tertiary education level. It shows most EFL writing teachers adopted existing western CT definitions in a general knowledge background and mainly used teacher-centered assessment techniques to teach CT. Students’ CT development was mostly assessed by self-designed CT assessments. Facing the globalization of CT teaching, the study thus updates the assessment techniques to meet the increasing needs of CT teaching in EFL writing in China. Relevant suggestions are also given to education practitioners.